1991
DOI: 10.1111/j.1365-2958.1991.tb01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an oxytetracycline‐resistance gene, otrA, of Streptomyces rimosus

Abstract: The sequence of a 2657 bp DNA fragment containing the coding and regulatory regions of the oxytetracycline (OTC)-resistance gene, otrA, from the OTC producer Streptomyces rimosus was determined. The predicted amino acid sequence of OtrA had extensive identity with tetracycline-resistance genes from other bacteria which mediate resistance via non-covalent ribosomal modification. The N-terminal domain had extremely high identity with the GTP-binding sites of elongation factors, such as EF-G and EF-Tu, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 44 publications
1
49
1
Order By: Relevance
“…The otr(A) gene was originally discovered on the chromosome of oxytetracycline producing Streptomyces rimosus (Ohnuki et al, 1985;Doyle et al, 1991). Subsequently, it has been found in Mycobacterium spp.…”
Section: Ribosomal Protection Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The otr(A) gene was originally discovered on the chromosome of oxytetracycline producing Streptomyces rimosus (Ohnuki et al, 1985;Doyle et al, 1991). Subsequently, it has been found in Mycobacterium spp.…”
Section: Ribosomal Protection Determinantsmentioning
confidence: 99%
“…In this regard, a tet gene is considered as a new tet gene when its gene product shows less than 80% amino acid identity to any so far known Tet protein (Levy et al, 1999). There is no essential difference between the tet and otr genes, but oxytetracycline resistance genes were first described in oxytetracycline producing organisms, which is reflected by the nomenclature (Ohnuki et al, 1985;Doyle et al, 1991).…”
Section: Mechanisms Of Tetracycline Resistancementioning
confidence: 99%
“…Previous research reported inhibitory effects of oxytetracycline on protein synthesis in bacteria through interference with the ternary amino-acyl-tRNA complex binding to the acceptor site of ribosomes [39], leading to retarded bacterial growth, disordered microbial community structure, and limited microbial ectoenzyme activity in the soil system [21,40]. Therefore, caution must be taken with the application of oxytetracycline to control fungal diseases, as it is antibiotic and impacts bacteria.…”
Section: Effects On Amino Acids and Protein Synthesismentioning
confidence: 99%
“…Three OTC (otr) genes encoding resistant determinants, designated otrA, otrB, and otrC, have been isolated from S. rimosus. OtrA protects the ribosome from translational arrest by tetracylines (61,167). Paralogues are present in other streptomycetes, e.g., Streptomyces lividans (58), and in tetracyclineresistant clinical infections (encoded by tetO and tetM).…”
Section: Cloning Of Tetracycline Resistance Genesmentioning
confidence: 99%
“…Restriction-deficient mutants (115) and broad-host-range plasmids (64,75,126,135) and phage vectors (208), including a bifunctional cosmid for use with S. rimosus, have also become available (40). These genetic tools and procedures have been applied to study the genetic instability of S. rimosus strains (49,80) and for the molecular cloning and characterization of the OTC resistance gene(s) (37,61,167,198) as well as the cloning of genes involved in OTC biosynthesis (29,36,37,150,177). These genes have also been used for the formulation of design rules for constructing hybrid aromatic polyketide synthases with a view to producing structural analogues, by combinato- rial biosynthesis, with potentially novel biological activities which are difficult to produce by traditional synthetic routes (125,148,175,177).…”
Section: Introductionmentioning
confidence: 99%